The importance of ritual initiation (Kgopha) as a passage for womanhood and the maintenance of marital life - Mapeke, Tlou Joyce (My University, 2004)
Refer to document
Thesis (M.A. (African Languages)) --University of Limpopo, 2004
Keywords: Ritual rights; Initiation songs; Initiation ceremonies; African - rituals; Initiation rites; Rites and ceremonies